Flow control and routing algorithms in WAPSN - Betini, Robert Cesar; Kameda, Hisao; Shimizu, Kentaro (Computer Communications, 1995)
The performance evaluation of several routing algorithms and the combined effect when four levels of flow control mechanisms are operating simultaneously in a wide area packetswitched network (WAPSN) is made by discrete-event simulation. Both non-adaptive and adaptive routing algorithms are discussed, and then the fixed (non-adaptive routing technique), the shortest-queue (isolated routing technique) and the shortest-path (distributed routing technique) routing algorithms are selected and described for simulation in networks both with and without a multilevel flow control mechanism. The flow control techniques described here are the channel queue limit, the window mechanism and the input buffer limit schemes. We give results for each of the following goals: 1. (a) To evaluate and compare the network performance of the routing algorithms under light, moderate and heavy load conditions during a transient period, subject to changes in the mean arrival rate of messages in networks both with and without a multilevel flow control mechanism. 2. (b) To evaluate and compare the performance of the routing algorithms during the transition of a network protected by an end-to-end flow control mechanism to an unprotected network. 3. (c) To evaluate the effect of varying the update interval for the adaptive routing algorithms. 4. (d) To evaluate and compare the performance of the routing algorithms in response to traffic changes or link failures in a network using a multilevel flow control mechanism. 5. (e) To develop innovative simulation models involving routing algorithms and a multilevel flow control mechanism for packet-switched networks.